Effects of a High-Protein Corn Product on Nutrient Digestibility and Production Responses in Mid-Lactation Dairy Cows - W. E. Brown; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2019)
An experiment was conducted to assess the effects of a high-protein corn product (56% crude protein; CP) relative to other sources of protein on the lactation performance of dairy cows. Twenty-four Holstein cows (1,367 ± 105 lb of body weight, 111 ± 34 days in milk, 2.28 ± 0.46 lactations; mean ± standard deviation) were randomly assigned to treatment sequence in a replicated 4 × 4 Latin square design balanced for carryover effects. Cows were individually fed one of four diets with a different protein concentrate source during each 28-day period, including: soybean meal (SBM), high-protein corn product (HPCP), soybean meal with rumen-bypass soy protein (SBMBP), and canola meal with rumen-bypass soy protein (CANBP). Diets were formulated for equal concentrations of CP and balanced to meet lysine and methionine requirements. The SBM diet was formulated to provide 5.7% rumen-undegradable protein (RUP), while SBMBP and CANBP diets were formulated for 6.8% RUP to match HPCP. The CANBP diet increased dry matter intake compared with SBM and HPCP. Treatment affected milk yield, as SBMBP and CANBP increased yield compared with SBM, but HPCP decreased milk yield compared to all treatments. HPCP reduced CP intake as a percent of total intake and increased the CP content of feed refusals, indicative of selection against HPCP. HPCP decreased apparent total tract CP digestibility, leading to less urine nitrogen excretion and greater fecal nitrogen output. SBMBP and CANBP performed equally in nearly every variable measured, except SBMBP increased milk urea nitrogen concentration. In conclusion, the HPCP diet reduced milk yield, milk component yields, urine nitrogen excretion, and increased fecal nitrogen excretion due to lesser total tract CP digestibility.
Keywords: milk yield; dietary protein; formulation